Parametric resonance of acoustic and optical phonons in GaAs/GaAsAl quantum well in the presence of laser field - Nguyen, Dung Tien; Trung, Le Canh; Duong, Pham Thi Hoai; Phong, Tran Cong (Photonics Letters of Poland, 2021)
In this paper, we analytically investigated the possibility of parametric resonance of acoustic and optical phonons. We obtained a general dispersion equation for parametric ampliﬁcation and transformation of phonons. The dispersions of the resonant acoustic phonon modes and the threshold amplitude of the ﬁeld for acoustic phonon parametric ampliﬁcation are obtained. The parametric ampliﬁcation for acoustic phonons in a GaAs/GaAsAl quantum well can occur under the condition that the amplitude of the external electromagnetic ﬁeld is higher than the threshold amplitude. Full Text: PDF References B. A. Glavin, V. A. Kochelap, T. L. Linnik, P. Walker, A. J. Kent and M. Henini, "Monochromatic terahertz acoustic phonon emission from piezoelectric superlattices", Journal of Physics: Conference Series, Vol 92, (2007). CrossRef O. A. C. Nunes, "Piezoelectric surface acoustical phonon amplification in graphene on a GaAs substrate", Journal of Applied Physics 115, 233715 (2014). CrossRef Yu. E. Lozovik, S. P. Merkulova, I. V. Ovchinnikov, "Sasers: resonant transitions in narrow-gap semiconductors and in exciton system in coupled quantum wells", Phys. Lett. A 282, 407-414, (2001). CrossRef R.P. Beardsley, A.V. Akimov, M. Henini and A.J. Kent, "Coherent Terahertz Sound Amplification and Spectral Line Narrowing in a Stark Ladder Superlattice", PRL 104, 085501, (2010). CrossRef Pascal Ruello, Vitalyi E. Gusev, "Physical mechanisms of coherent acoustic phonons generation by ultrafast laser action", Ultrasonics 56, 21-35, (2015). CrossRef L. Esaki, in Proc. 17th Int. Conf. Phys. Semiconductors, San Francisco, CA, Aug, J.D. Chadi and W.A. Harrison, Eds, Berlin: Springer- Verlag, 473, (1984). DirectLink W. Xu, F. M. Peeters and J. T. Devreese, "Electrophonon resonances in a quasi-two-dimensional electron system", Phys. Rev. B 48, 1562 (1993). CrossRef Tran Cong Phong, Nguyen Quang Bau, "Parametric resonance of acoustic and optical phonons in a quantum well", Journal of the Korean Physical Society, Vol. 42, No. 5, 647-651, (2003). DirectLink